1999
DOI: 10.1063/1.480062
|View full text |Cite
|
Sign up to set email alerts
|

Electronic absorption spectra of linear C6, C8 and cyclic C10, C12 in neon matrices

Abstract: Erratum: "Electronic absorption spectra of carbon chain anions C 2n − (n=4-7) in neon matrices" [J.The electronic absorption spectra of the even-numbered carbon molecules C 6 -C 14 have been measured in neon matrices. Bare carbon anions were produced in a cesium sputter source, mass selected, codeposited with neon at 6 K, and neutralized. The spectra show, apart from the known ͑1͒ 3 ⌺ u Ϫ ←X 3 ⌺ g Ϫ transition of linear C 6 , C 8 , and C 10 in the visible, absorption bands in the UV region. The spectral data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 36 publications
2
49
0
Order By: Relevance
“…Mass spectrometric techniques are usually employed to detect them after their generation, for example by laser evaporation of graphite or from stable organic precursors [102]. To study this unique form of carbon by electronic and/or vibrational spectroscopy in the gas phase or under matrix isolation conditions would be extremely interesting [103]. It has been estimated that the deformation of the bond angle at each sphybridized carbon atom of cyclo-C 18 112 amounts to ca.…”
Section: Scheme 716mentioning
confidence: 99%
“…Mass spectrometric techniques are usually employed to detect them after their generation, for example by laser evaporation of graphite or from stable organic precursors [102]. To study this unique form of carbon by electronic and/or vibrational spectroscopy in the gas phase or under matrix isolation conditions would be extremely interesting [103]. It has been estimated that the deformation of the bond angle at each sphybridized carbon atom of cyclo-C 18 112 amounts to ca.…”
Section: Scheme 716mentioning
confidence: 99%
“…390 9 Carbon-Rich Compounds: Acetylene-Based Carbon Allotropes Figure 9.1 UV/Vis absorption spectra of laser-ablated carbon clusters C n trapped in a solid Ne matrix at 5 K (by T. W., collaboration with Prof. Dr. Takamasa Momose, Kyoto University). The assignment of bands by analogy with the literature [5,6,27,28]. The relatively sharp peak with an asterisk at 407 nm is the A 1 P u nX 1 S g + transition of C 3 [1,2,4,28].…”
Section: Linear Carbon Clustersmentioning
confidence: 99%
“…For mass-selected C 10 -trapped in a solid Ne matrix, Grutter et al suggested that the UV band at 316 nm (see Figure 9.1) is attributable to cyclic C 10 rather than to linear C 10 [27]. The assignment is based on extrapolation of the calculated excitation energy for cyclic C 6 to the energy for cyclic C 10 at the MRD-CI (multi-reference single and double excitation configuration interaction) level of theory [24].…”
Section: Linear Carbon Clustersmentioning
confidence: 99%
“…Results from infrared spectroscopy [3][4][5] and surface-enhanced Raman spectroscopy 6,7 are available for neutral carbon clusters, but few experiments have been performed for molecules larger than C 13 . The linear isomers of neutral C 4 to C 10 have been verified by ESR measurements in neon matrixes. 8 In addition, electronic absorption spectra of matrix-isolated neutral C n clusters 9,10 have produced evidence of linear chain structures for C 4-C 10 and of cyclic structures for C 10-C 14 neutral species.…”
Section: Introductionmentioning
confidence: 99%